Проблемні аспекти правового регулювання діяльності центрів надання адміністративних послуг - Крикавська, І. В.; Krykavska, I. V.; Крикавская, И. В. (Видавництво Львівської політехніки, 2019)
Висвітлено поняття та правовий статус спільних, виїзних та мобільних центрів надання адміністративних послуг. Розглянуто проблемні аспекти двох підходів до створення спільних центрів надання адміністративних послуг і запропоновано шляхи їх вирішення. Досліджено правове регулювання надання електронних послуг та роль ЦНАП у цьому процесі.

The article is devoted to the interpretation of the concepts and legal status of “common”, “outgoing” and “mobile” Administrative Service Centers, as well as the electronic providing of administrative services. The decentralization of power is being actively pursued, which is to delegate most of the powers to local governments. The quality of providing administrative services is one of the most important factors that will affect the effectiveness of change and build public confidence in local governments and public authorities. Since the inception of the Administrative Service Centers, these have evolved significantly to this day. New realities leads to the emergence of problematic aspects of their legal regulation and the needs for further improvement of regulatory acts. Legal regulation of the functioning of “common”, “outgoing” and “mobile” Administrative Service Centers requires adaptation of the Ukrainian legislation to the requirements of the present, consolidation of the their legal status. It is necessary to define to the Law of Ukraine “About Administrative Services” the unified approach to the concepts of “common”, “outgoing” and “mobile” Administrative Service Centers. The problematic aspects of two approaches to the creation of “common” Administrative Service Centers are considered and the ways of their solution are suggested. An approximate memorandum of understanding for a “common” Administrative Service Centers is needed to outline all the major issues of interaction. The legal regulation of the providing of electronic services and the role of Administrative Service Centers in this process are investigated. Reforming and providing electronic administrative services considerable experience in organizing processes, on such problematic aspects as protection of personal information in the Internet, equal access to citizens regardless of welfare and others.

Статья посвящена толкованию понятий и правового статуса совместных, выездных и мобильных центров предоставления административных услуг. Рассмотрены проблемные аспекты двух подходов к созданию совместных центров предоставления административных услуг и предложены пути их решения. Исследовано правовое регулирование предоставления электронных услуг и роль ЦНАП в этом процессе.
Problemic aspects of the legal regulation of the administrative services centers activities
Проблемные аспекты правового регулирования деятельности центров предоставления административных услуг
Keywords: адміністративна послуга; центр надання адміністративних послуг; administrative service; Administrative Service Centers; административная услуга; центр предоставления административных услуг; 342.9